Neonatal Cardiac ECMO in 2019 and Beyond - Roeleveld, Peter Paul; Mendonca, Malaika (Frontiers in Pediatrics, 2019)
Worldwide, the use of Extracorporeal Membrane Oxygenation (ECMO) for cardiac failure has been steadily increasing in the neonatal population and has become a widely accepted modality. Especially in centers caring for children with (congenital) heart disease, ECMO is now an essential part of care available for those with severe heart failure as a bridge to recovery, long term mechanical support, or transplantation. Short-term outcomes depend very much on indication. Hospital survival is approximately 40% for all neonatal cardiac ECMO patients combined. ECMO is being used for pre- and/or postoperative stabilization in neonates with congenital heart disease and in neonates with medical heart disease such as myocarditis, cardiomyopathy or refractory arrhythmias. ECMO use during resuscitation (ECPR) or for sepsis is summarized elsewhere in this special edition of Frontiers in Pediatrics. In this review article, we will discuss the indications for neonatal cardiac ECMO, the difficult process of patients´ selection and identifying the right timing to initiate ECMO, as well as outline pros and cons for peripheral vs central cannulation. We will present predictors of mortality and, very importantly, predictors of survival: what can be done to improve the outcomes for your patients. Furthermore, an overview of current insights regarding supportive care in neonatal cardiac ECMO is given. Additionally, we will address issues specific to neonates with single ventricle physiology on ECMO, for example cannulation strategies and the influence of shunt type (Blalock-Taussig shunt versus “right ventricle to pulmonary artery” shunt). We will not only focus on short term outcomes, such as hospital survival, but also on the importance of long-term neuro-developmental outcomes, and we will end this review with suggestions for future research.